1993
DOI: 10.1021/bi00087a020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the DNA binding domain of gene V protein encoded by bacteriophage M13 with the aid of spin-labeled oligonucleotides in combination with proton NMR

Abstract: The DNA binding domain of the single-stranded DNA binding protein gene V protein encoded by the bacteriophage M13 was studied by means of 1H nuclear magnetic resonance, through use of a spin-labeled deoxytrinucleotide. The paramagnetic relaxation effects observed in the 1H-NMR spectrum of M13 GVP upon binding of the spin-labeled ligand were made manifest by means of 2D difference spectroscopy. In this way, a vast data reduction was accomplished which enabled us to check and extend the analysis of the 2D spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…The sequences of these turns are : Glu4S-(Xaa),-Pro49-AlaSO-Gly51 in Pf3 ssDBP, and AspSO-(Xaa),-AlaS7-ProS8-Gly59 in Ff GVP. Contrary to AspSO in Ff GVP, residues 57-59 appear not to be involved in DNA binding nor protein-protein interactions (Folkers et al, 1993;Folmer et al, 1994), so their sequence similarity is probably of structural rather than functional relevance. In Fig.…”
Section: Comparison With the Ff Gene V Proteinmentioning
confidence: 93%
See 1 more Smart Citation
“…The sequences of these turns are : Glu4S-(Xaa),-Pro49-AlaSO-Gly51 in Pf3 ssDBP, and AspSO-(Xaa),-AlaS7-ProS8-Gly59 in Ff GVP. Contrary to AspSO in Ff GVP, residues 57-59 appear not to be involved in DNA binding nor protein-protein interactions (Folkers et al, 1993;Folmer et al, 1994), so their sequence similarity is probably of structural rather than functional relevance. In Fig.…”
Section: Comparison With the Ff Gene V Proteinmentioning
confidence: 93%
“…Most of these residues are situated at the same side of the hairpin (Argl6, Gly18, Ser20, and Tyr26 of the Ff protein, and Argl2, Gly14, Serl6, Tyr22 of Pf3); the residues protruding to the other side are less well conserved (except for Pro2.5). DNA binding studies performed on Ff GVP have indicated that the surface formed by residues Argl6, Gly18, Ser20, Tyr26 and Leu28 is involved in the interaction with the DNA (Folkers et al, 1993). Therefore, it is likely that the corresponding residues in Pf3 ssDBP also form part of the DNA binding domain.…”
Section: Comparison With the Ff Gene V Proteinmentioning
confidence: 99%
“…More detailed studies regarding the interactions between GVP and DNA have been carried out (reviewed in Kansy et al, 1986). In particular, NMR and fluorescence spectroscopies have implicated several amino acids of GVP that are in contact with DNA in the GVP-ssDNA complex (King & Coleman, 1987Dick et al, 1989;Stassen et al, 1992;Folkers et al, 1993).…”
mentioning
confidence: 99%
“…6E) and a new salt bridge between D50 and R80 is formed. In our model of the GVP-ssDNA complex (Guan et al, 1995), R80 is involved in the interaction between ssDNA and GVP (Folkers et al, 1993). So a movement of R80 will influence the It is of interest to note that the hydrophobic L32 is found on the surface of the p-core near the dimer-dimer contact loop.…”
Section: Discussionmentioning
confidence: 96%
“…During the rolling circle replication process, GVP binds to the ssDNA cooperatively and, ultimately, a superhelical GVP-DNA complex is formed. The structure of such helical complexes has been studied by a number of biophysical methods, including electron microscopy (Gray, 1989;Olah et al, 1995), neutron scattering (Gray et al, 1982;Olah et al, 1995), NMR and fluorescence spectroscopies (King & Coleman, 1987Dick et al, 1989;Stassen et al, 1992;Folkers et al, 1993). The results of these studies have provided valuable insights regarding the interactions of GVP and ssDNA.…”
mentioning
confidence: 99%